Landscape Spatial Analysis for Sustainable Land Use Planning: A Two-Scale Approach to the Seville Metropolitan Area - Feria Toribio, José María; Santiago Ramos, Jesús (Journal of planning education and research, 2022)
Metropolitan areas are complex, dynamic spatial systems. This paper sets out a spatial analysis methodology suitable to address the internal complexity of metropolitan landscape change and which results could be useful for decision making in the context of sustainable land use planning. A two-scale approach is adopted for the analysis of recent land use changes in the metropolitan area of Seville (Spain), being the methodology applied to both the whole metropolitan area and two different landscape units. Distinct landscape change patterns and urban growth models are identified for the units studied. On the basis of the results, the convenience of a multiscale planning approach is highlighted.